Pengaturan Retribusi dalam Undang-Undang Nomor 28 Tahun 2009 dan Undang-Undang Nomor 1 Tahun 2022 - Elisabeth Margreta Sibuea (Pusat Riset dan Inovasi Nasional, 2025)
In the current era of regional autonomy, regions are given greater authority to regulate and manage their own households. The objectives, among others, are to bring government services closer to the community, make it easier for the community to unite and control the use of funds sourced from the Regional Budget and Expenditure (APBD), different incomes to create healthy competition between regions and encourage innovation. In 2022, Law no. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. The law changes more or less the arrangements related to regional levies. How are the changes that have occurred, especially in the regulation of levies between Law No. 28 of 2009 and Law No. 1 of 2022.